Molecular Phylogeny of the Lizard Clade Leiosaurae Endemic to Southern South America - Morando, Mariana (2015)
The clade Leiosaurae currently includes 18 species in the genera Diplolaemus, Leiosaurus, and Pristidactylus. It is mainly distributed in Argentina from 30u latitude south in the northwestern region of the country, to 52u south in Patagonia, from 63u longitude in coastal areas to 73u along the Andean Cordillera, across multiple habitats and including a small area in Chile. Several morphological and molecular taxonomic studies on a subset of these species have been published, but no comprehensive phylogenetic hypothesis is available for the clade. The objective of this work is to present a molecular phylogenetic hypothesis for the majority of the described species in the clade. We sequenced two mitochondrial genes, five nuclear protein coding, and three anonymous nuclear loci, and implemented traditional concatenated analyses as well as a species-tree approach. All methods inferred very similar topologies. We found the genera Diplolaemus and Leiosaurus to be monophyletic, whereas P. torquatus was retrieved as a separate lineage from the other Pristidactylus species with strong statistical support. Within Diplolaemus, D. darwinii is a very distinct lineage with an estimated divergence time of ,14.74 million yr ago (mya). Based on an early Miocene Leiosaurae fossil mandible, we estimated the crown common ancestor of the genus Leiosaurus at ,9.24 mya, and L. bellii is the earliest divergent lineage within this genus. The Argentinean Pristidactylus species seem to have radiated relatively recently (4.02 mya). A combination of geological and climatic events during Middle and Late Miocene, and climatic changes associated with glaciations, most probably played a role in the divergence of the Leiosaurae clade. The diversification patterns of Diplolaemus and Leiosaurus seem to have followed a general south-to-north direction, while the Argentinean Pristidactylus may have diversified east-to-west and north-to-south. We suggest that morphological and thermophysiological studies combined with palaeo-niche modeling analyses are needed to test these hypotheses and better understand the biogeographical history of this clade.